Criminological Characteristic of a Modern Cyber Offender in the Russian Federation - Andrey BAYBARIN; Alexander GREBENKOV; Vladimir TARYKIN; Gennady PLOHIH; Anton BAUMSTEIN (Communications of International Proceedings, 2020)
The article is devoted to the study of the quantitative and qualitative characteristics of computer crime in the Russian Federation, which, together with a detailed analysis of the criminological parameters of a cybercriminal's personality, made it possible to substantiate the main trends that have formed over the past 5 years in this area. Particular attention is focused on the analysis of statistical indicators presented by the Judicial Department at the Supreme Court of the Russian Federation for the period 2015-2019, which made it possible to draw up a typical criminological portrait of the personality of a Russian computer criminal.
Keywords: computer crime; cybercrime; criminological characterization; information and communication technologies; typology; computer offender.